Modern deformations of earth crust of territory of Western Ukraine based on «Geoterrace» GNSS network data - Третяк, Корнилій; Брусак, Іван; Tretyak, Kornyliy; Brusak, Ivan (Видавництво Львівської політехніки, 2028)
У роботі проаналізовано сучасні тенденції горизонтальних та вертикальних зміщень території заходу України за ГНСС-даними, з побудовою відповідних карт рухів та з виділенням зон деформацій верхнього шару земної кори. Об’єктом дослідження є горизонтальні та вертикальні деформації верхнього шару земної кори. Мета – виявлення та аналіз деформаційних зон на Заході України. Вихідними даними є горизонтальні та вертикальні швидкості 48 ГНСС-станцій з 2018 до 2021 років мережі “Geoterrace” на Заході України, відомі тектонічні карти території та описові матеріали. Методика передбачає порівняння та аналіз сучасних деформацій земної кори регіону з його відомою тектонічною структурою. У результаті вперше побудовано карти горизонтальних швидкостей ГНСС-станцій та деформацій верхнього шару земної кори Заходу України як єдиного регіону і вертикальних швидкостей ГНСС-станцій. Встановлено, що деформації території Заходу України є складними і лише частково співвідносяться з відомою тектонічною будовою в регіоні. Більшість ГНСС-станцій зазнають висотних просідань, імовірно, в зв’язку з денудаційними процесами, але Галицько-Волинська западина практично не просідає. На схилах Українського щита помітна кореляція вертикальних зміщень та глибини залягання поверхні кристалічних порід. Зони стиску виділяються на Закарпатті, що відповідає території Закарпатського глибинного розлому, а інша – на північному-заході регіону. Окремо необхідно виділити регіон довкола міста Хмельницький, де спостерігаються аномальні вертикальні та горизонтальні зміщення. Подано геодинамічну інтерпретацію аномальних зон деформацій. Визначені швидкості ГНСС-станцій зі збільшенням часового інтервалу спостережень дадуть можливість встановити особливості просторового розподілу руху земної кори на території Заходу України та в майбутньому створити відповідну регіональну геодинамічну модель.

The work analyzes the current horizontal and vertical displacement territory of western Ukraine according to GNSS data, including the creation of special maps of modern displacements and the allocation of deformation zones of the upper crust. The object of study is the horizontal and vertical deformations of the upper crust. The aim is to identify and analyze deformation zones in Western Ukraine. The initial data are horizontal and vertical velocities of 48 continuous GNSS stations from 2018 to 2021 of Geoterrace network, known tectonic maps of the territory and descriptive materials. The methods include comparison and analysis of modern Earth crust deformations of the region with its known tectonic structure. As a result, for the first time it was possible to create the maps of horizontal velocities of continuous GNSS stations and deformations as well as vertical velocities of GNSS stations of the upper crust of Western Ukraine as a whole region. It is established that the deformations of the territory of Western Ukraine are complex and only partially correlate with the known tectonic structure in the region. Most continuous GNSS stations subside in vertical components, possible due to denudation processes. The Galicia–Volyn depression, however, practically does not subside. On the slopes of the Ukrainian Shield there is a noticeable correlation of vertical displacements and the depth of the surface of crystalline rocks. Zones of compression are identified in Zakarpattia, which corresponds to the Zakarpathian (Transcarpathian) deep fault, and in the north-west of the region. It is necessary to mark the zone around the city of Khmelnytskyi, where abnormal vertical and horizontal displacements are observed. Geodynamic interpretation of anomalous deformation zones is given. Determined velocities of continuous GNSS stations with the increasing observation time interval will make it possible to establish the features of the spatial distribution of Western Ukraine crustal movement as well as create an appropriate regional geodynamic model in the future.
Сучасні деформації земної кори території Заходу України за даними ГНСС мережі «Geoterrace»
Keywords: сучасна геодинаміка; деформації земної кори; ГНСС-дані; Захід України; modern geodynamics; deformations of the Earth crust; GNSS data; Western Ukraine; 551.24; 528.22